A study on diagnostic efficacy of pulmonary imaging tool in patients with rheumatoid arthritis - Gantait, Kripasindhu; Gantait, Ishita; Islam, Jamirul; Sarkar, Tuhinsubhra (International Journal of Research in Medical Sciences, 2019)
Background: Pulmonary complication in Rheumatoid arthritis is major health concern in the field of rheumatology. So this study is to find out the sensitive imaging tool for detecting different types of pulmonary changes seen in RA. Methods: This is a comparative, analytical, cross sectional, Institution- based, single centre study. We included all adult willing patients of Rheumatoid arthritis (age >18) and selected them based on 2010 ACR/EULAR criteria. Severity was assessed by number of joints involve in both upper and lower limb, along with ESR, CRP, Anti CCP level. Chest x ray, PFT and HRCT thorax were done in all RA patients. Results: Out of 50 RA patients, pulmonary involvement was observed in 25 patients identified by Spirometry, CXR, HRCT. Pulmonary involvement is more common in age group <40 years. Most common form of pulmonary involvement is ILD followed by obstructive lung disease like chronic bronchitis, bronchiectasis etc. HRCT is the most common tool for detection of Pulmonary involvement in rheumatoid arthritis. HRCT abnormality, most are Restrictive on spirometry (FEV1/FVC) <80% of predicted value. And this relation is statistically significant as P value is 0.001 (<0.05) by Chi-Square test. Patients having more the disease duration, more the pulmonary involvement. This association is statically significant as p value is 0.001 (<0.05). Conclusions: High resolution CT thorax is more sensitive modality for detection of pulmonary pathology in rheumatoid arthritis. Because of its high cost, availability of this imaging technique is beyond the lower socio-economic group where chest x ray may be useful.